Developing a multimodal maternal infant perinatal outpatient delivery system: the MOMI PODS program - Bose Brill, Seuli; Juckett, Lisa A.; D’Amico Gordon, Rachel; Thomas, Nikki; Bunger, Alicia; Fareed, Naleef; Voisin, Christiane; Flores, Paola; Mao, Shengyi; Benninger, Kristen L.; Grobman, William; Panchal, Bethany; et al. (Frontiers in Global Women's Health, 2023)
Progress in maternal child health has been hampered by poor rates of outpatient follow up for postpartum individuals. Primary care after delivery can effectively detect and treat several pregnancy-related complications and comorbidities, but postpartum linkage to primary care remains low. In this manuscript, we share the experience of implementing a novel mother-infant dyad program, the Multimodal Maternal Infant Perinatal Outpatient Delivery System (MOMI PODS), to improve primary care linkage and community resource access postpartum via integration into pediatric care structures. With a focus on providing care for people who are publicly insured, we designed a program to mitigate maternal morbidity risk factors in postpartum individuals with chronic disease or pregnancy complications. We discuss the systematic process of designing, executing, and evaluating a collaborative clinical program with involvement of internal medicine/pediatric, family medicine, and obstetric clinicians via establishing stakeholders, identifying best practices, drawing from the evidence base, designing training and promotional materials, training partners and providers, and evaluating clinic enrollment. We share the challenges encountered such as in achieving sufficient provider capacity, consistent provision of care, scheduling, and data tracking, as well as mitigation strategies to overcome these barriers. Overall, MOMI PODS is an innovative approach that integrates outpatient postpartum care into traditional pediatric structures to increase access, showing significant promise to improve healthcare utilization and promote postpartum health.